Understanding Financial Digitization: From Creativity to Innovation and Competition among MSMEs - Rachmawati, Irma; Yulianti, Eka Budi; Junianto, Pilifus; Ramadhan, Ramadhan; Nugroho, Febriawan Ardi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study discussed the meaning of financial digitalization from creativity to innovation and competition in small and medium enterprises. The authors believe that digital financial and small business success is related to the era of technology and competition. In other words, the ability of business drivers to empower technology in financial activities. To discuss the theme of this study, we have conducted digital data searches on both national and international publication databases consisting of literature, journals, magazines, and website literature. To complete this discussion, we examine the data in-depth under a phenomenological approach, namely an effort to explore the data as broadly as possible to understand valid and up-to-date answers to questions. Based on the findings and discussion data, we conclude that financial digitization uses the latest technology that allows the financial function to have a high impact in today's technological and competitive business era. Therefore, this finding is a valuable input for future digital financial studies and business activities.